Muscle Efficiency Changes during Successful and Unsuccessful Trials in Elite Pistol Shooters: Mediating Role of Quiet eye Meditation - Amir Shahavand; Khajavi Daryoush; Alireza Bahrami; Ahmad Ghotbi Varzaneh (University of Tehran, 2021)
The purpose of current study was to muscle efficiency changes during successful and unsuccessful trials in elite pistol shooters with role of quiet eye meditation. In causal comparative study, 20 elite male pistol shooters selected for this study with age range 20-30 years old. After five trials familiarization, participants performed 20 trials to target with available standard. Scores of ten were considered successful, and scores of less than ten were considered unsuccessful. Data were analyzed using paired t-test and Bootstrap. The results indicated that there was significant difference between biceps and triceps muscle activity in successful and unsuccessful trials, and participants had lower muscle activity in successful trials than unsuccessful trials. Also, Bootstrap results revealed that the quiet eye period mediates biceps and triceps muscle activity in successful and unsuccessful trials. Overall, the results of current study confirmed postural stability hypothesis that this is the determining factor during this period is an increase in postural stability, which leads to a reduction in "noise" in the motor system.Shooting skills with high perceptual / cognitive requirements and low mobility needs and is one of the sports that is highly dependent on the performance of the visual system, because target identification and tracking is largely dependent on the performance of the visual system.In the present study, the researcher intends to investigate the muscular efficiency and mediating role of the length of the stationary eye period in the electrical activity of biceps and triceps of skilled pistol shooters in successful and unsuccessful attempts.